Lokalitas Kitab Tafsir Qoeran Djawen - Zainab, Zainab (Aqwal: Journal of Qur'an and Hadis Studies, 2021)
The process of interpreting the Qur'an is not only limited to the practice of understanding a text by a mufasir. More than that, a mufasir engages in a dialogue with existing traditions, culture and socio-politics. Likewise, studying interpretation in Indonesia, especially Java, also concerns the socio-political conditions of the writer, the audience space when the interpretation is written, the language used and the purpose of writing the interpretation are some important studies to be explored. In Java, there are quite a number of interpreters with the characters of their respective interpretations, one of which is the Tafsir Qoeran Djawen book. In this interpretation, it accommodates various local aspects such as script, narrative and communication in the practice of interpretation. Departing from this, the author raises the title ""Locality of the Book Tafsir Qoeran Djawen"". This study focuses on the locality contained in the Tafsir Qoeran Djawen. The results of this study, namely, the form of locality in this interpretation can be seen in its appearance and communication as described above. Namely the interpretation using the cacarakan script and krama inggil. Meanwhile, the locality aspect, in its interpretation, the author of the book Tafsir Qoeran Djawen interprets the verses of the Al-Qur'an by including local elements that exist in Javanese society, such as traditions and culture in society, events that intersect with society and others. Some examples of aspects of locality in the interpretation presented in the Tafsir Qoeran Djawen book, for example discussing the pilgrimage tradition, mentioning Javanese philosophy, criticizing the tahlilan tradition and others.